A literature review of 'best practice' for radiographers when imaging suspected non-accidental injury or physical abuse of children in Australia and New Zealand. (March 2020) - Doyle, Edel; Vuong, Raymond
Highlights: Best practice guidelines were reviewed from the USA, UK, New Zealand and Melbourne, Australia. Similar approaches observed but not standardised between imaging departments. Australia requires a national guideline to achieve consistent image quality.